STEGANOGRAFI PADA CITRA BITMAP MENGGUNAKAN METODE LEAST SIGNIFICANT BIT BERSILANG UNTUK TEKS TERENKRIPSI BASE64 - Albert Christie Giovani; Yustina Retno Wahyu Utami; Teguh Susyanto (Jurnal Ilmiah SINUS, 2019)
The development of internet has become one of the most popular data communication media. The ease of use and complete facilities are the advantages possessed by the internet. However, along with the development of internet media and applications that use the Internet,  crime on information system increases as well. With various illegal information-gathering techniques developing, many are trying to access information that is not their right. There are several security techniques for sending messages confidentially and securedly, one of which is known as steganography. This study combined steganography and cryptography. The message was encrypted first using base64 then inserted using the LSB Crossed method. This method was aimed at making the process of extracting messages by unauthorized ones not easy. Embedding message into images was using the last binary number of the RGB value of an image by randomizing the placement of binary numbers by integrating base64 coding so that it combined base64 messages which next the text messages would be encrypted. The measurement results in the stego image using PSNR (Peak Signal to Noise Ratio) showed that the image quality after the insertion process was > 50 db